Clinical Course Score (CCS): a new clinical score to evaluate efficacy of neurotrauma treatment in traumatic brain injury and subarachnoid hemorrhage - Brandner, Sebastian; Kellermann, Isabel; Hore, Nirjhar; Bozhkov, Yavor; Buchfelder, Michael (Journal of Neurosurgical Anesthesiology, 2015)
Neurotrauma continues to represent a challenging public health issue requiring continual improvement in therapeutic approaches. As no such current system exists, we present in this study the Clinical Course Score (CCS) as a new clinical score to evaluate the efficacy of neurotrauma treatment.The CCS was calculated in neurotrauma patients to be the difference between the grade of the Glasgow Outcome Scale 6 months after discharge from our department and the grade of a 1 to 5 point reduced Glasgow Coma Scale on admission. We assessed the CCS in a total of 248 patients (196 traumatic brain injury [TBI] patients and 52 subarachnoid hemorrhage [SAH] patients) who were treated in our Department of Neurosurgery between January 2011 and December 2012.We found negative CCS grades both in mild TBI and in mild SAH patients. In patients with severe TBI or SAH, we found positive CCS grades. In SAH patients, we found higher CCS scores in younger patients compared with elderly subjects in both mild and severe cases.The CCS can be useful in evaluating different therapeutic approaches during neurotrauma therapy. This new score might improve assessment of beneficial effects of therapeutic procedures.
EVALuna2:22862

Early CSF and Serum S100B Concentrations for Outcome Prediction in Traumatic Brain Injury and Subarachnoid Hemorrhage - Kellermann, Isabel; Kleindienst, Andrea; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Clinical Neurology and Neurosurgery, 2016)
OBJECTIVES: S100B has been proposed as a putative biochemical marker in determining the extent of brain injury and corresponding prognosis in neurotrauma. The aim of this study was to evaluate the prognostic value of S100B early concentrations in serum and cerebrospinal fluid (CSF) in traumatic brain injury (TBI) and subarachnoid hemorrhage (SAH), to determine prognostically relevant threshold values and to evaluate fluctuation following EVD placement. PATIENTS AND METHODS: In 102 patients (45 SAH and 57 TBI) under intensive care unit (ICU) treated between January 2011 and December 2012 with external ventricular drain (EVD) S100B measurements were performed simultaneously in serum and CSF during the first 5 days and before and after EVD exchange. Glasgow coma scale (GCS) was assessed on admission and Glasgow outcome scale (GOS) 6 months later. RESULTS: Peak S100B levels in CSF and serum were measured on the first day after admission and concentrations decreased during the ensuing days post injury gradually. CSF and serum S100B concentrations in TBI patients were significantly higher than in SAH (p<0.005). Both in TBI and SAH patients S100B concentrations in CSF and serum were significantly higher in patients with an unfavorable outcome (GOS 1-3) in comparison to patients with a good outcome (GOS 4-5). Correlation of S100B concentrations in serum and GOS score at 6 months was significant both in TBI and SAH (p<0.05). Serum S100B concentrations >0.7μg/l correlated with 100% mortality. Correlation between S100B in CSF and GOS was significant in SAH (p<0.05), whereas it was not significant in TBI. After EVD exchange (n=53) we found a significant increase of S100B concentration in CSF (p<0.005). CONCLUSION: Initial S100B levels have a limited prognostic value in neurotrauma with CSF concentrations being highly sensitive to smallest influences like EVD placement. However, high initial S100B levels of >0.7μg/dl in serum are associated with 100% mortality, which might help to guide therapy strategies in severe neurotrauma.
EVALuna2:33856